Improved genetic prediction of complex traits from individual-level data or summary statistics - Qianqian Zhang (Nature Portfolio, 2021)
Existing genetic prediction tools typically assume that genetic variants contribute equally towards the phenotype. The authors develop eight prediction tools that allow the user to specify the heritability model, and show that these tools enable substantially improved prediction of complex traits.